Sociedade, educação infantil e conhecimento científico : o ensino sobre o Cerrado e a metodologia TiNis na Pré-escola - Cunha, Patricia Moreira da (2023)
The Cerrado occupies 23.9% of the national territory, with awide diversity of animal and plant species. Several researches, Silva (2018), Vieira Filho(2016), point out that due to the advance of the agricultural frontier, driven by monocultureagribusiness, it has caused immense transformation of the biome, mainly in the first twodecades of the 21st century. Thus, it becomes evident that, given this reality, there is a need towork on the Cerrado theme in the classroom from Kindergarten, the first stage of BasicEducation. However, it is essential that teachers have didactic resources at hand and that theyhave attractive methodologies to teach and raise awareness about the importance of itspreservation. Within this perspective, the central question was to understand how the TiNismethodology, which aims to encourage children and adolescents to develop empathy forplanting, can contribute as a learning methodology that transforms reality. The objectives wereorganized into two. A general one, which sought to assess whether the TiNis methodology andthe didactic sequence are efficient tools in teaching about the Cerrado in the context of EarlyChildhood Education. And the specific ones are the following: Apply a didactic sequencereferring to teaching about the Cerrado in pre-school within the BNCC/DC-GO proposal;demonstrate that it is possible to develop the Cerrado theme in preschool; demonstrate through research carried out on social networks how the TiNis methodology is being applied in Brazilby people and companies/schools and present and apply the TiNis methodology to awaken theinterest of preschool students enrolled in the children's group V about the importance of naturepreservation. To achieve these objectives, the methodology used was the application of aninterview before and after the didactic sequence and the development of the TiNis methodologyto verify whether the students acquired or expanded their knowledge about the Cerrado. Thecollected information data were analyzed using Laurence Bardin's content analysis method. Theproject was developed with the participation of two classes enrolled in kindergarten V so thatone acted as a control group, participating only in the didactic sequence on teaching the Cerradoand the other participated in the didactic sequence and also in the implementation of the TiNismethodology. At the end of the research, it was possible to conclude that the knowledgereached by the participants was similar, showing that the didactic sequence contributedsignificantly to working on the Cerrado theme in Early Childhood Education, and the TiNismethodology proved to be an engaging alternative for children to act ludic and attractive in theconstruction of knowledge.